PENGARUH PENDEKATAN OPEN ENDED PROBLEM TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII - Sirwanti Sirwanti; Riska Riska (Didaktika : Jurnal Kependidikan, 2019)
This study aims to determine how the influence of the open-ended problem approach to the students’ mathematics learning outcomes at grade VII SMP Muhammadiyah Walattasi, Soppeng Regency. The researcher used 2 classes; experimental and control class. This study used a Nonequivalent Control Group Design with quasi-experimental type. The research population is students of grade VII SMP Muhammadiyah Walattasi, Soppeng Regency. Learning outcome data is processed using independent T-test samples through normality prerequisite tests (Kolmogorof Smirnov) and homogeneity tests for variance in statistical tests with significance level (α = 0 .05). Data were processed by utilizing SPSS version 23 software. The results of hypothesis testing indicated that Tcount Ttable or 4,561 2,011, like to see sig data. (2 tailed) the experimental class and the control class 0,000 0.05, Based on these results, it could be conclude that there is an influence of the open-ended problem approach to the students’ mathematics learning outcomes at grade VII SMP Muhammadiyah Walattasi, Soppeng Regency. Kata Kunci: open-ended problem; Students’ Mathematics learning outcome